The fisheries dissipative effect modelling through dynamical systems and chaos theory - Ferreira, M. A. M. (2014)
It is presented a very simple mathematical model to study the dissipative effect in fisheries, based in dynamical systems and in its approach through chaos theory. Actually, due to constant misconducts, forgetting their consequences and only prosecuting easy profits, the risk of extinction is very real for fisheries resources. From it results the importance of this kind of models.